Analisis Faktor Dominan yang Memengaruhi Pemilihan Fasilitas Kesehatan Tingkat Pertama (FKTP) oleh Peserta BPJS Kesehatan di Kabupaten Tob - Martha Silalahi; Ernita Sicila Ritonga; Soriata Simamora (Jurnal Kesehatan Sejahtera, 2026)
Optimizing the function of Primary Health Facilities (FKTP) as gatekeepers for the National Health Insurance (JKN) in rural areas, such as Toba Regency, still faces the challenge of unequal utilization. This quantitative cross-sectional study analyzed the dominant factors influencing BPJS Kesehatan participants' preferences in selecting FKTPs. The study sample included 391 respondents selected using a proportionate random sampling technique. Data were collected using a structured questionnaire and then analyzed univariately, bivariately using the Chi-Square test, and multivariately using Multiple Logistic Regression. The bivariate test results showed that all independent variables were significantly associated with FKTP selection (p-value <0.05). Based on the multivariate analysis, perceived service quality was the most dominant factor, with the highest Odds Ratio (OR) of 4.12 (95% CI: 2.34–7.25). The next dominant factors were the availability of health workers and medicines (OR = 2.85), and waiting time for services (OR = 2.11). In conclusion, participant preferences are largely determined by subjective assessments of the quality of clinical services and medical support facilities. Therefore, local governments and the BPJS Kesehatan (Social Security Agency for Health) need to standardize service quality and ensure equitable distribution of medication and healthcare workers across rural primary care facilities (FKTP) to prevent patient congestion.